Morphological, anatomical and preliminary phytochemical characterization of Buddleja madagascariensis Lam. - Dobriyal, Vaishali; Guleri, Saurabh; Singh, Maneesha (Current Botany, 2021)
Buddleja madagascariensis Lam. is a perennial invasive shrub distributed in tropical and sub-tropical regions of the world. The present study was conducted on morphological, anatomical and phytochemical characterization of Buddleja madagascariensis and the results revealed that plant height varied from about 188-191 cm, and the whole plant was covered with trichome which may be glandular and eglandular and unicellular or, multicellular. Inflorescence was terminal and axillary in position, thyrsoid panicle. Anatomical and histo-chemical studies of the transverse section of various parts of the plant revealed the presence of steller tissues, starch in cortical and pith region. Phytochemical analysis of the crude extract showed the presence of carbohydrates, proteins, saponins, flavonoids, phenolic compounds and tannins. But alkaloids, glycosides and free amino acids were absent. Thus, characterization of plants on the basis of these parameters could be used as tools to distinguish the crude drugs of plants from adulterants, used in the preparation of traditional medicines and used as diagnostic keys. Also, it is useful in the future for revealing the importance of plants and phytochemical resources for the conservation of resources.